Economic potential assessment of rare earth extraction sequence based on rule-based framework - M. Y. M., Yunus; Nurul Ain, Ismail; Badhrulhisham, Abdul Aziz (Faculty Mechanical Engineering, UMP, 2018)
Rare Earth Element (REE) is a unique group of metals which mainly comprises seventeen (17) elements, which fifteen (15) elements from the lanthanides group plus Scandium and Yttrium. This REE can be divided into heavy rare earth element (HREE) and light rare earth element (LREE) categories. During the initial extraction stage, the LREE is separated from HREE of the original ore and the sub-separations are then conducted subsequently corresponding to the respective categories. However, the separation difficulty becomes rather critical in a certain context, whenever the HREE is the major element to be extracted relative to LREE. In addition, there are no systematic guidelines procedures available to determine which specific separation pathway is more economically feasible among the various extraction options that exist. Thus, this study proposes a systematic quantitative rule-based framework, by excel modelling, in assessing comprehensively the economic potential of any separation model of REE processing that considered, whereby the standard characterization of monazite mineral composition is utilized as the main case study. This work also adopts the separation factor value of HDEHP-HCL as well as EHEHPA-HCL as the main extraction platforms. The findings suggest that the former extractant is effective for the extraction of light REE (LREE), while the latter incline to prefer the medium and heavy REE (MREE and HREE) particularly on the ground of separation stages factor. In light of the initial results, this study also proposes a hybrid approach in performing the complete optimal REE separation that specifically based on the sequence of ‘Art versus Science’ (AvsS) structure. These results have demonstrated that the proposed quantitative rule-based framework able to determine the optimal separation pathway provided the complete separation factor values and the mineral characterization of REE are available for assessment. Thus, this new method is suitably applied as a tool or guidelines in the feasibility study of any processing design for REE separation.